Precise mapping of subunits in multiprotein complexes by a versatile electron microscopy label - Flemming, Dirk; Thierbach, Karsten; Stelter, Philipp; Böttcher, Bettina; Hurt, Ed (Nature structural & molecular biology, 2010)
While the topological analysis of protein complexes by electron microscopy (EM) has developed in recent years, the exact position of single subunits within multisubunit complexes has been difficult. A new clonable peptide tag, which when attached to a target protein can recruit a structurally prominent label that is easily identifiable by EM, may help solve this problem.